2022
DOI: 10.1186/s13068-022-02159-1
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the world’s largest elephant population in search of ligninolytic microorganisms for biorefineries: a mini-review

Abstract: Gastrointestinal tracts (GIT) of herbivores are lignin-rich environments with the potential to find ligninolytic microorganisms. The occurrence of the microorganisms in herbivore GIT is a well-documented mutualistic relationship where the former benefits from the provision of nutrients and the latter benefits from the microorganism-assisted digestion of their recalcitrant lignin diets. Elephants are one of the largest herbivores that rely on the microbial anaerobic fermentation of their bulky recalcitrant low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…The ecosystems are affected by geology, geomorphology, and climate which have a direct impact on the flora and, consequently, the fauna, including insects and their associated yeasts symbionts (Scholes & Biggs, 2004). Furthermore, studies on herbivorous mammals including elephants and rhinos and associated insects such as dung beetles within the region report a wide diversity of microbiota (Nwaefuna, Boekhout, et al, 2023; Rammala & Zhou, 2022). Since yeasts thrive in exudates from leaves, roots, flowers, and tree trunks (Cadete et al, 2014; Starmer & Lachance, 2011), the diversity of ecosystems in southern Africa predicts the presence of many novel yeasts.…”
Section: The Southern African Environment: Factors That Could Possibl...mentioning
confidence: 99%
“…The ecosystems are affected by geology, geomorphology, and climate which have a direct impact on the flora and, consequently, the fauna, including insects and their associated yeasts symbionts (Scholes & Biggs, 2004). Furthermore, studies on herbivorous mammals including elephants and rhinos and associated insects such as dung beetles within the region report a wide diversity of microbiota (Nwaefuna, Boekhout, et al, 2023; Rammala & Zhou, 2022). Since yeasts thrive in exudates from leaves, roots, flowers, and tree trunks (Cadete et al, 2014; Starmer & Lachance, 2011), the diversity of ecosystems in southern Africa predicts the presence of many novel yeasts.…”
Section: The Southern African Environment: Factors That Could Possibl...mentioning
confidence: 99%
“…African elephants are hindgut, colonic fermenters and subsist on a diet of mainly grass and the twigs, leaves and fruits of trees and shrubs in their grazing area (Buss, 1961; Greene et al., 2019). Their mechanism of feeding, that is, the fermentation of raw plant materials with the aid of gut microbiota, has sparked interest from a biotechnological perspective, as environmentally sustainable methods for plant material degradation are in demand from industries such as the pulp and paper industry (Rammala & Zhou, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to find sustainable solutions to the degradation of lignocellulytic and pectin biomass have focused on mining the gut and fecal microbiomes of natural digesters such as elephants ( L. africana ), yaks ( Bos grunniens ) and cows ( Bos indicus ) for potential microbes and CAZymes (Gong et al., 2020; Khatoon et al., 2022; Rammala & Zhou, 2022). Indeed, the mining of an 18‐year‐old Asian elephant's metagenome showed that its fecal metagenome was geared toward biomass degradation and in particular carbohydrate degradation with the identification of 11 novel GH families (Jakeer et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation